2022
DOI: 10.1002/jpen.2333
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fecal microbial transplant on intestinal microbial composition in short‐bowel neonatal piglets

Abstract: Background Short‐bowel syndrome (SBS) in neonates is associated with microbial dysbiosis due to intestinal surgery, prolonged hospitalization, enteral nutrition, and repeated antibiotic exposure. Sepsis and liver disease, leading causes of morbidity and mortality in SBS, may relate to such intestinal dysbiosis. We investigated the safety and feasibility of fecal microbial transplant (FMT) to alter intestinal microbial composition in SBS piglets. Methods Following a 75% distal small‐intestinal resection, piglet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…one week after the FMT, may be considered as a limit of this experiment. A recent study reported that FMT on SBS piglets induced only transient changes to their intestinal microbiota that did not persist after 5 days (Hinchliffe et al, 2022). Furthermore, colonization by a "dysbiotic" microbiota from animals on HFD is transient if the diet is not maintained (Tomas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…one week after the FMT, may be considered as a limit of this experiment. A recent study reported that FMT on SBS piglets induced only transient changes to their intestinal microbiota that did not persist after 5 days (Hinchliffe et al, 2022). Furthermore, colonization by a "dysbiotic" microbiota from animals on HFD is transient if the diet is not maintained (Tomas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the resolution of these challenges and questions will allow us to design individualized strategies which are focused on the gut microbiota’s composition and function for the prevention of TPN-related gastrointestinal diseases in the pediatric population, improving their clinical outcomes when long-term PN is required. In this regard, for instance, there are still many challenges regarding the safety and effectiveness of a fecal microbiome transplant in order to restore the gut microbiota in humans, although promising short-term clinical outcomes have been obtained in animal models of SBS fed with PN [ 211 ]. Interestingly, this new knowledge must be considered in updated guidelines in order to strongly recommend the use of prebiotics, probiotics, synbiotics, postbiotics and paraprobiotics as an adjunctive therapy in the prevention and treatment of PN-related diseases.…”
Section: Conclusion Challenges and Future Directionsmentioning
confidence: 99%
“…Rectal administration is the most preferable method of administering FMT, since oral FMT administration increases lethal sepsis incidence and overall mortality by exposing the proximal gut to potentially pathogenic organisms ( 66 ). However, according to another study, intragastric administration of FMT appears safe in postsurgical newborn piglets with SBS, with no sepsis and no mortality ( 67 ). Hence, there is a need to further explore the security of administration of FMT by different routes.…”
Section: Necrotizing Enterocolitis Treatment Strategymentioning
confidence: 99%